MSME Development Strategy in Pekarungan village - Adhani, Nency Febri; Pujianto, Wahyu Eko (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. I carry out this community service in Pekarungan Village in Sukodono District, Sidoarjo Regency. Purpose. This village is one of 16 villages in Sukodono District which has the potential for the MSME sector which operates in various business sectors. Pekarungan Village has 225 MSMEs which have great potential to improve the community's economy. One of the potential areas of MSMEs in Pekarungan Village is the culinary center or MSMEs. Method. The method that I will use for this research is a qualitative method by processing primary and secondary data. Through this program, I want to advance and develop the MSME sector in Pekarungan village by implementing MSME development strategies. Results. Culinary in Pekarungan village is still facing several business development problems. These problems are related to ownership, capital and lack of knowledge about product innovation and financial management. Conclusion. GANEFA peanut brittle has its own unique taste with very unique topping variants. According to one buyer, this peanut brittle is different from the others in terms of packaging and this peanut brittle is good. So peanut brittle is one food that can increase the market price significantly if it has good packaging.